Technology and the Wage Structure - Allen, Steven G. (Journal of Labor Economics, 2001)
This article reports direct evidence on how technological change is related to changes in wage gaps by schooling, experience, and gender. Wage gaps by schooling increased the most in industries with rising R&D intensity and accelerating growth in the capital‐labor ratio. Estimates of their relationship to high‐tech capital are inconclusive. Contrary to popular notions that technological change harms older workers, wage growth of experienced workers is much greater in R&D‐intensive industries than in industries with little R&D activity. The gender gap narrowed more in industries that most intensively used high‐tech capital in 1979.